Effects of a parenting intervention to address maternal psychological wellbeing and child development and growth in rural Uganda: a community-based, cluster-randomised trial - Dr. Daisy R Singla, PhD; Elias Kumbakumba, MMed; Prof. Frances E Aboud, PhD (Elsevier, 2015)
Background: Parenting interventions have been implemented to improve the compromised developmental potential among 39% of children younger than 5 years living in low-income and middle-income countries. Maternal wellbeing is important for child development, especially in children younger than 3 years who are vulnerable and dependent on their mothers for nutrition and stimulation. We assessed an integrated, community-based parenting intervention that targeted both child development and maternal wellbeing in rural Uganda. Methods: In this community-based, cluster randomised trial, we assessed the effectiveness of a manualised, parenting intervention in Lira, Uganda. We selected and randomly assigned 12 parishes (1:1) to either parenting intervention or control (inclusion on a waitlist with a brief message on nutrition) groups using a computer-generated list of random numbers. Within each parish, we selected two to three eligible communities that had a parish office or a primary school in which a preschool could be established, more than 75 households with children younger than 6 years, and at least 15 socially disadvantaged families (ie, maternal education of primary school level or lower) with at least one child younger than 36 months. Participants within communities were mother-child dyads, where the child was 12-36 months of age at enrolment, and the mother had low maternal education. In the parenting intervention group, participants attended 12 fortnightly peer-led group sessions focusing on child care and maternal wellbeing. The primary outcomes were cognitive and receptive language development, as measured with the Bayley Scales of Infant Development, 3rd edn. Secondary outcomes included self-reported maternal depressive symptoms, using the Center for Epidemiologic Studies Depression Scale, and child growth. Theoretically-relevant parenting practices, including the Home Observation for Measurement of the Environment inventory, and mother-care variables, such as perceived spousal support, were also assessed as potential mediators. Baseline assessments were done in January, 2013, and endline assessments were done in November, 2013, 3 months after completion of the programme. Ethics approval was received from Mbarara and McGill universities. This trial is registered with ClinicalTrials.gov, NCT01906606. Findings: Between December, 2012, and January, 2013, 13 communities (194 dyads) were randomly assigned to receive intervention, and 12 communities (154 dyads) were assigned to a waitlist control. 319 dyads completed baseline measures (171 in the intervention group and 148 in the control group), and 291 dyads completed endline measures (160 in the intervention group and 131 in the control group). At endline, children in the intervention group had significantly higher cognitive scores (58·90 vs 55·65, effect size 0·36, 95% CI 0·12-0·59) and receptive language scores (23·86 vs 22·40, 0·27, 0·03-0·50) than did children in the control group. Mothers in the intervention group reported significantly fewer depressive symptoms (15·36 vs 18·61, −0·391, −0·62 to −0·16) than did mothers in the control group. However, no differences were found in child growth between groups. Interpretation: The 12 session integrated parenting intervention delivered by non-professional community members improved child development and maternal wellbeing in rural Uganda. Because this intervention was largely managed and implemented by a local organisation, using local community members and minimal resources, such a programme has the potential to be replicated and scaled up in other low-resource, village-based settings. Funding: Plan Uganda via Plan Finland (Ministry of Foreign Affairs) and Plan Australia (Australian Aid).